REFORMA ADMINISTRATIVA DO ESTADO DO MARANHÃO: expressões do neoliberalismo na política educacional no período de 1995 a 2002. - Bastos, James Dean Brito (2012)
This study is in the line of research State and Educational Management. It analyzed the impacts of economic transformations and their impact on educational guidelines implemented in 1990, in the sense to adapt the educational structure demands from big capital. In trying to understand the part, I mean, the expressions of neoliberalism in education policy in the State of Maranhão in the period 1995 to 2002, total, initially characterized the State, politics, Crises of Capital, the reform of the State, the Catholic Reform and its consequences within national educational and local. We discuss about the economic and political biases in Maranhão to perceive the presence of the multiple determinants of macro policy in the administrative structure of Maranhão and forwards provided on basic educational policy. The Organization of this research took in historical-critical approach, since the reality is contradictory and multifaceted and this poll has the fundamental interest of bringing the most studied reality. Accordingly, while methodological procedure made sure the use of documentary and bibliographic research, through field more or less structured interview. In bibliographic search worked with several authors, among which we highlight: Marx (1983), Coggiola (2009), Lenin (2010), Kosík (1976), Frigotto (1999), Mészáros (2005), Shiroma (2007), Silva (2001) and Luz Junior (2009). Showed that in the design of the subject of the search, there was an intense process of precarization teaching and teaching work in public school education, I mean, in infrastructure and working, in the form of temporary teachers ' contracts, wage conditions of temporary teachers. It was noted that the understanding of the subject of research in the foreground by the hand of Government was the great leap of quality in basic education of Maranhão by the subject of the research leaders and researchers perceive antagonistically analysis existed educational policy as a mechanism of permanence and deepening insecurity teaching and teaching work, because the main goal was to the quantitative aspect of registrations and the generation of school flow that would immediately on loans the Federal Government and world organisms.